(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: The significance of some infection sources, pathways of pathogen transmission and etiological structure of diarrhea infections (DI) have changed. Many issues of DI epidemiology are still insufficiently studied, which prevents the organisation of quality epidemiological surveillance and diseases control. Objectives: To study the DI epidemic situation (ES) in North- Eastern Ukraine and to identify the factors that determines the characteristics of epidemic process (EP). Material and Methods: The reports of Ministry of Health of Ukraine (1960- 2018) and Head Statistics Administration of Sumy Oblast (2001-2018) have been used. The biological properties of 40 strains of K. pneumoniae, 50 - S. aureus, 40 - E. cloacae recovered from the feces of patients with DI have been studied Results: It has been found that the EP of DI is characterized by a sharp decrease in the incidence of typhoid fever and shigellosis, increase in the incidence of salmonellosis and dominance of DI caused by other specified or unspecified pathogens (SDI and UDI) in the nosological structure (p<0.05). The incidence of DI caused by Klebsiella, Staphylococus, Enterobacters exceeds the incidence of salmonellosis, shigellosis, typhoid fever (p<0.05). Opportunistic pathogens (OP), which are pathogens of DI have antilysozyme activity and adhesion ability, which proves their pathogenic potential. The demographics indirectly affect the incidence of DI. Access to water supply, sewerage, hot water supply is correlates with the incidence of DI. Conclusion: The system of epidemiological surveillance over DI in Ukraine needs improvement by optimisation its information and analytical subsystems aimed at objective epidemiological diagnostics and ES forecasting. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.420-426